Vascular co-option in resistance to anti-angiogenic therapy - Ribatti, Domenico; Annese, Tiziana; Tamma, Roberto (Frontiers in Oncology, 2023)
Three different mechanisms of neovascularization have been described in tumor growth, including sprouting angiogenesis, intussusceptive microvascular growth and glomeruloid vascular proliferation. Tumors can also grow by means of alternative mechanisms including vascular cooption, vasculogenic mimicry, angiotropism, and recruitment of endothelial precursor cells.Vascular co-option occurs in tumors independently of sprouting angiogenesis and the nonangiogenic cancer cells are described as exploiting pre-existing vessels. Vascular co-option is more frequently observed in tumors of densely vascularized organs, including the brain, lung and liver.Vascular co-option represents one of the main mechanisms involved in metastasis, as occurs in liver and lung, and resistance to anti-angiogenic therapy. The aim of this review article is to analyze the role of vascular co-option as mechanism through which tumors develop resistance to antiangiogenic conventional therapeutic approaches and how blocking co-option can suppress tumor growth.